Sustainability and innovation in Spain: Fuzzy set qualitative comparative analysis (FSQCA) in IBEX35 companies - Castelló Sirvent, Fernando (2021)
This study analyzes the configuration of sustainability in Spanish public opinion. Furthermore, this study evaluates the success strategies of the main companies of the Spanish stock index IBEX 35 to increase their media representation in terms of sustainability and innovation. The article evaluates the different recipes followed by the IBEX 35 companies during 2019 through a Fuzzy Set Qualitative Comparative Analysis (fsQCA) based on economic and media attributes. Economic conditions include market capitalization, Price Earning Ratio (PER), and free float. The media conditions include thematic and media concentration, as well as the association of news with industries and companies.